Efeito in vitro da associação de CXCL10 com Glucantime® em macrófagos RAW 264.7 infectados por Leishmania infantum - Santos, Priscilla Nascimento dos (2018)
Visceral leishmaniasis (VL) is the gravest form of leishmaniasis caused by the genus Leishmania, and is characterized by the loss of the host's ability to generate an effective immune response. Chemokines have direct involvement in the pathogenesis of leishmaniasis, and may potentially be used as adjuvants in the treatment of such diseases. CXCL10 is a chemokine that has shown promising results in the treatment of leishmaniasis. The objective of this study was to verify the in vitro effect of the association of CXCL10 with Glucantime®on RAW 264.7 macrophages infected by L. infantum.RAW 264.7 macrophages were infected with L. infantum in vitro and treated or not with CXCL10 (25, 50 and 100 ng/ mL), Glucantime® (16 mg/mL) and CXCL10+Glucantime® (25, 50 and 100 ng/mL) + (16 mg/mL). Parasite load in infected macrophages, as well as nitric oxide (NO), IL-12, TNF-α, IL-4 and IL-10 production in the supernatants of macrophages were assessed at 24h and 48h after infection.It was observed that both CXCL10 and CXCL10 + Glucantime®, in the three concentrations used, showed a significant reduction of the parasite load in the infected macrophages, with a decrease in the concentration of 100ng/mL, 74% and 75%, respectively, and this reduction was greater than that induced by Glucantime® (50%).When the cells were treated with CXCL10 alone, the reduction in the number of intracellular parasites was correlated with the increase in NO, however, in contrast, in the association with Glucantime®, even with reduction of the parasitic load, there was a decrease in NO production, as the concentration of CXCL10 was increased.Regarding the cytokines, it was observed that CXCL10 and the association with Glucantime® induced higher concentrations of IL-12 and TNF-α, and lower IL-10 and IL-4, when compared to Glucantime®, suggesting the induction of a important profile Th1.Collectively, data from this work suggest an immunoprotective role of CXCL10, associated or not to Glucantime®, in RAW 264.7 macrophages infected by L. infantum. Data from this study may also provide information for the development of future therapeutic interventions for visceral leishmaniasis, using CXCL10 as adjuvant withGlucantime®.